URETHRAL DUPLICATION A RARE CAUSE OF EVEN RARER DORSAL CHORDEE - Naveed Ahmed (Pakistan Armed Forces Medical Journal, 2021)
Chordee is a condition in which the penile head has a curvature. It can be towards ventral or dorsal aspect. Dorsal chordee is very rare. In many normal males mild degrees of curvature can exist. Causes of dorsal chordee can be diverse but urethral duplication as its etiology is even rarer. We report a case of six year old boy who presented with severe dorsal chordee with associated double urethra and cleft of the glans dorsally without hypospadia.